2012
DOI: 10.1111/j.1749-124x.2012.12000.x
|View full text |Cite
|
Sign up to set email alerts
|

Creeping Tiger, Soaring Dragon: India, China and Competition in Information Technologies

Abstract: Although conventional international economic wisdom holds China's hardware and India's software industries to be equipotential, little attempt has been made to compare their information industries in an overarching dynamic framework. Using a schema that links intellectual to financial value creation, it is found that China has systematically moved ahead in creating a self‐supporting industrial and innovation ecosystem. Hardware enjoys higher barriers to entry, which the Chinese companies are increasingly reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…We excluded research papers that not reported case studies (Bonvillian, 2014; Carayannis, 2014; Carayannis and Campbell, 2011; Chea, 2008; Fukuda and Watanabe, 2008; Gobbe, 2014; Hawk et al , 2012; Huhtamäki et al , 2011; Nambisan, 2013; Rubens et al , 2011; Samila and Sorenson, 2010; Smulders, 2013; Traitler et al , 2011; Watters, 2013; Yilmaz, 2011; Zahra and Nambisan, 2011; Chandran and Sundram, 2014; Faraj et al , 2012; Chidambaram, 2014; Heller, 2013) or qualitative case studies (Chaudhuri, 2012; Volkova and Jakobsone, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…We excluded research papers that not reported case studies (Bonvillian, 2014; Carayannis, 2014; Carayannis and Campbell, 2011; Chea, 2008; Fukuda and Watanabe, 2008; Gobbe, 2014; Hawk et al , 2012; Huhtamäki et al , 2011; Nambisan, 2013; Rubens et al , 2011; Samila and Sorenson, 2010; Smulders, 2013; Traitler et al , 2011; Watters, 2013; Yilmaz, 2011; Zahra and Nambisan, 2011; Chandran and Sundram, 2014; Faraj et al , 2012; Chidambaram, 2014; Heller, 2013) or qualitative case studies (Chaudhuri, 2012; Volkova and Jakobsone, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…He cites a lack of government commitment to R&D, inadequate links between different types of organizations, and 'official neglect' of the country's universities (Krishna 2013). Focusing on information and telecommunications technologies in particular, Anindya Chaudhuri sees India as lagging far behind the United States and increasingly behind China as well (Chaudhuri 2012). He suggests that the Indian government makes too little effort to ensure that the R&D activities conducted by foreign firms in India generate positive spillovers for the country more generally.…”
Section: The Unimpressedmentioning
confidence: 98%
“…In other ways, however, they do seem to be developing at very different rates. Relying on a range of different indicators, several scholars have emphasized that China has progressed farther and faster than India, albeit to different degrees (Dahlman 2010;Chaudhuri 2012;Altenburg et al 2008).…”
Section: New Directionsmentioning
confidence: 99%
“…The key references are articles in (international) economics and business journals (Barba Navaretti & Venables, 2004;Melitz, 2003;Wagner, 2007). The literature specifically focused on developing countries is predominantly centred on China and India (Chaudhuri, 2012;Franco, Ray, & Ray, 2011;P. P. Li, 2007;Zhang & Zhang, 2003).…”
Section: International Trade and Foreign Direct Investment (Fdi)mentioning
confidence: 99%